Application of continuous type pilot-scale superheated steam roasting system for production of ready-to-eat (RTE) chicken - Kim, Cho Yeon; Kim, Ye Won; Park, Sung Hee (Food science and biotechnology, 2025)
In this study, we evaluate the feasibility of a pilot-scale continuous superheated steam (SHS) roasting system for ready-to-eat (RTE) chicken production. SHS roasting was tested at different temperatures (75, 85, and 95 °C) and times (5, 10, and 15 min). SHS roasting of chicken at 85 °C for 5 min resulted in a thermal dose of 160.37 ± 1.78 k °C s, which was equivalent to that (172.15 ± 29.55 k °C s) achieved for roasting at 75 °C for 10 min. The thermal dose equivalence indicated that rapid SHS treatment at a high roasting temperature was more efficient than long-term SHS treatment at a low temperature. The most appropriate roasting condition was 85 °C for 5 min, achieving a desirable moisture content level and hardness. SHS roasting at 75 °C for 5 min showed the highest throughput (57.68 ± 2.58 units/h). Thus, this study demonstrated the potential of a continuous SHS roasting system for RTE chicken product production on an industrial scale with appropriate combinations of roasting temperature and time. The online version contains supplementary material available at 10.1007/s10068-025-01913-z.